Association between serum netrin-1 levels and early neurological deterioration after acute ischemic stroke - Chen, Zhuo; Cao, Tianli; Zhong, Xingju; Wu, Yong; Fu, Wei; Fan, Chaoli; Jiang, Yu; Zhou, Qi; Peng, Jie; Liao, Jieyu; You, Zhike; Yi, Xin; et al. (Frontiers in Neurology, 2022)
Background and Purposes: Experimental studies demonstrated that netrin-1 (NT-1) has anti-inflammatory, tissue regeneration, and immune modulation properties. We aimed to discern the utility of NT-1 as a biomarker for assessing the risk of early neurological deterioration (END) after ischemic stroke. Methods: This was a prospective study enrolling ischemic patients with symptoms onset < 24 h. Serum NT-1 concentrations were measured at admission. A National Institutes of Health Stroke Scale increased by ≥2 points and ≥4 points during the first 72 h after admission was defined as END2 and END4, respectively. Results: The study included 268 patients (146 males and 122 females) with a mean age of 63.0 ± 9.6 years. The median NT-1 concentrations were 466.4 pg/mL (interquartile range, 341.4–589.2 pg/mL). During the initial 72 hours after admission, END2 was found in 83 (31.0%) patients, and END4 was observed in 48 (17.9%) subjects. After adjusted for potential confounders, multivariate analysis indicated that decreased NT-1 levels is an independent predictor for END2 [odds ratio (OR) 0.62, 95% confidence interval (CI) 0.46–0.84, P < 0.001) and END4 (OR 0.53, 95% CI 0.36–0.76, P < 0.001). Similar results were found when the NT-1 levels were analyzed as a categorical variable. Furthermore, restricted cubic spline analysis showed a linear association between NT-1 concentrations and the risk of END (END2, P = 0.006 for linearity; END4, P < 0.001 for linearity). Conclusions: Our results suggest that decreased NT-1 levels were significantly associated with a higher risk of END after ischemic stroke.